Optimasi Proses Sand Blasting Terhadap Laju Korosi Hasil Pengecatan Baja Aisi 430 - Setyarini, Putu Hadi (Rekayasa Mesin, 2011)
Corrosion is naturally occuring phenomenon and will be exist by itself in the metal. The metal will be damaged by an electrochemical reaction with its environment and can not eliminated but can do a variety of prevention efforts, such as by using a barrier layer that is in the process of painting. In the process, the quality of painting is paint adhesion influenced by surface roughness. The preparation can be done by themethod of spraying a sand blasting abrasive material in the form of sand forced into the surface of the material. sand blasting process could make the paint more durable and more resistant to corrosion. The parameter used in this study were sand blasting spraying pressure i.e 4;4,5;5;5,5 bar, sand blasting spraying angle 600; 750; 900. The results showed that the greater the pressure and angle of sand blasting, the corrosion rate is lower Average corrosion rate of the lowest occured at 5 bar spraying pressure and 900 spraying angle were 7.2157-E5; 7.1157-E5; 6.95-E5 mpy Keywords : sand blasting, corrosion.